Gender in Discourse Analysis: Moroccan and Algerian Literature as a Case Study - Rachida Sadouni (The Journal of Studies in Language, Culture and Society, 2019)
The present paper deals with Moroccan and Algerian post-colonial literature written by women. It will specifically approach the issue of gender as seen and analyzed by four female novelists: Leila Abou Zeid, Zahra Ramidj, Malika Mokeddem and Maissa Bey. We will attempt to exemplify gender as for stereotypes, (in) equality and roles. Ranging from reality to fiction and from self-history to social-History, our paper commits itself to present an evolution of women as objects/subjects, at individual, social and historical backgrounds. Through this research, we reached the results that in the four novels, Algerian and Moroccan women are in constant fight for their emancipation in their respective patriarchal societies.